Symptomatic severe hypophosphatemia after intravenous ferric carboxymaltose. Issue 5 (27th March 2019) - Fang, Wendy; McMahon, Lawrence P; Bloom, Stephen; Garg, Mayur
Abstract : Intravenous iron is commonly prescribed for treatment of iron deficiency, with modern formulations demonstrating an acceptable safety profile in the majority of patients. We report the case of a patient who was hospitalised with muscle pain, deteriorating mobility and multiple fractures following repeated ferric carboxymaltose infusions. Investigations revealed severe hypophosphatemia with serum phosphate of 0.27 mmol/L, 25‐hydroxyvitamin D (25OHD) level of 32 nmol/L and insufficiency fractures of the sacrum and L5 transverse process. The patient's hypophosphatemia was corrected with several infusions of intravenous phosphate, as well as oral phosphate and calcitriol, with subsequent resolution of her muscle aches, back pain and immobility. The risk of persistent hypophosphatemia and osteomalacia may be higher with iron carboxymaltose than other iron formulations and a transient increase in intact fibroblast growth factor‐23 with reduced renal tubular phosphate absorption has been postulated as the key mechanism. This risk appears increased by repeated iron infusions, underlying malnutrition, hypophosphatemia at baseline, vitamin D deficiency, hyperparathyroidism or anti‐resorptive medication use. The true risk and incidence of hypophosphatemia need to be clarified so that appropriate monitoring, prevention and treatment strategies can be developed. Abstract : A 73‐year‐old woman with anemia due to portal hypertensive gastropathy and gastric antral vascular ectasia was hospitalized with severe symptomatic hypophosphatemia and fractures after recurrent ferric carboxymaltose infusions. Asymptomatic hypophosphatemia has been previously described after ferric carboxymaltose in several large trials; however, this case demonstrates that some patients may also develop severe symptomatic hypophosphatemia. Monitoring of serum phosphate levels in certain patients receiving ferric carboxymaltose should be considered, especially if they have previously experienced side effects; are having recurrent infusions; or in the presence of other risk factors for hypophosphatemia, such as concurrent use of antiresorptive medications, malnutrition, vitamin D deficiency, and baseline hypophosphatemia.